Competing in Architecture. Crowdsourcing as a Research Tool - Newton, Clare; Backhouse, Sarah (FormAkademisk, 2013)
Architectural competitions are powerful strategies for generating visual ideas for new futures. Academic research generates new knowledge based on rigorous investigations of informed propositions. This paper describes an unusual merging of a research process with a competition process using crowdsourcing to leverage knowledge. The Australian Research Council (ARC) is the pre-eminent funding body of academic research for universities across Australia. In 2010 a multidisciplinary academic team, with twelve industry partners including six education departments, successfully sought ARC research funding. The application proposed an unprecedented strategy to include an open Ideas Competition in the middle year of a three-year research program as a form of crowdsourcing to leverage knowledge between academia and industry. The research project, entitled Future Proofing Schools, was focused on Australia’s relocatable school buildings.